2019
DOI: 10.32942/osf.io/8qavw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental effects on the covariation among pace-of-life traits

Abstract: A range of life-history strategies along a slow-fast continuum emerge due to trade-offs between allocation to current and future reproduction. Pace-of-life syndromes (POLS) are suites of correlated life-history, physiological and behavioral traits that arise due to these trade-offs. The notion that correlations among traits may vary between populations of the same species or along environmental gradients suggests an important role for the environment in shaping and maintaining POLS. Understanding how environme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…resource) dependent, this could generate positive within‐individual correlations between behaviour and both survival probability and reproduction, as observed here. Although two recent meta‐analyses have demonstrated that resource acquisition influences behavioural expression within individuals (Dougherty, 2021a, 2021b), empirical work estimating the relationships between behaviour, survival, and reproduction simultaneously across environmental gradients of resource availability are needed to test this idea explicitly (Montiglio et al ., 2018; Hämäläinen et al ., 2021). Our results nonetheless indicate that variation in resource acquisition may play a more important role in shaping behaviour–fitness co‐variances than currently captured by theory.…”
Section: Discussionmentioning
confidence: 99%
“…resource) dependent, this could generate positive within‐individual correlations between behaviour and both survival probability and reproduction, as observed here. Although two recent meta‐analyses have demonstrated that resource acquisition influences behavioural expression within individuals (Dougherty, 2021a, 2021b), empirical work estimating the relationships between behaviour, survival, and reproduction simultaneously across environmental gradients of resource availability are needed to test this idea explicitly (Montiglio et al ., 2018; Hämäläinen et al ., 2021). Our results nonetheless indicate that variation in resource acquisition may play a more important role in shaping behaviour–fitness co‐variances than currently captured by theory.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that integrate plastic (within population) and evolutionary (among populations) responses to time constraints are needed to clarify this intriguing, contrasting pattern. With time constraints being a ubiquitous stressor in natural populations, our work is among the few to address the recent call to test POLS across relevant ecological gradients (Dammhahn et al 2018, Hämäläinen et al 2020). Our results thereby add new insights and suggest that, besides the predicted plastic changes in life history means, also plastic changes in behavioural trait integration may be an important but overlooked adaptive aspect of responding to seasonal time constraints.…”
Section: Discussionmentioning
confidence: 99%
“…How environmental stressors shape the strength and consistency of trait integration and the repeatability of traits is highly debated (Killen et al 2013, Montiglio and Royauté 2014, Hämäläinen et al 2020). On the one hand, environmental stressors such as predation stress can establish new (or enhance already present) trait correlations, as shown among behavioural traits (Bell and Sih 2007, Adriaenssens and Johnsson 2013), possibly to achieve an optimal trait combination that would increase fitness under these new conditions (Sih et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the recent literature on these topics have evaluated relationships between traits and environments across species (e.g., Fulton et al 2001, Case et al 2004, Trebilco et al 2015, Hämäläinen et al 2020, Mortelliti and Brehm 2020; relatively few studies have examined variation in phenotype-environment covariance in detail, and within a single species (see Zamudio et al 2016 and references therein).…”
Section: -Introductionmentioning
confidence: 99%